Experimentally determining the exchange parameters of quasi-two-dimensional Heisenberg magnets - Goddard, P; Singleton, J; Sengupta, P; McDonald, R; Lancaster, T; Blundell, S; Pratt, F; Cox, S; Harrison, N; Manson, J; Southerland, H; Schlueter, J (IOP Publishing, 2008)
Though long-range magnetic order cannot occur at temperatures T > 0 in a perfect two-dimensional (2D) Heisenberg magnet, real quasi-2D materials will invariably possess nonzero inter-plane coupling J⊥ driving the system to order at elevated temperatures. This process can be studied using quantum Monte Carlo calculations. However, it is difficult to test the results of these calculations experimentally since for highly anisotropic materials in which the in-plane coupling is comparable with attainable magnetic fields J ⊥ is necessarily very small and inaccessible directly. In addition, because of the large anisotropy, the Néel temperatures are low and difficult to determine from thermodynamic measurements. Here, we present an elegant method of assessing the calculations via two independent experimental probes: pulsed-field magnetization in fields of up to 85 T, and muon-spin rotation. We successfully demonstrate the application of this method for nine metalorganic Cu-based quasi-2D magnets with pyrazine (pyz) bridges. Our results suggest the superexchange efficiency of the [Cu(HF2) (pyz) 2]X family of compounds (where X can be ClO4, BF 4, PF6, SbF6 and AsF6) might be controlled by the tilting of the pyz molecule with respect to the 2D planes. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.